Balancing Driver Workloads Through Two-Stage Service Area Assignment in Last-Mile Delivery - Jang, Jin-Myeong; Mei, Hangyu; Kim, Hwa-Joong (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
This study addressed a two-stage delivery assignment problem in e-commerce with short- and mid-term planning phases. The mid-term phase groups small service areas into core areas and assigns them to drivers. These core areas are refined in the short-term phase by allocating unassigned areas based on mid-term results. This study aims to assign service areas to drivers to minimize delivery time while balancing workloads under preferences and practical constraints. It is formulated by extending traditional districting models. This study proposes two heuristic algorithms. The Relax-and-Fix heuristic relaxes decision variables to solve subproblems, then gradually fixes them to construct an initial solution. The Fix-and-Optimize heuristic fixes variable subsets and applies local search for improvement. Computational experiments using real-world data demonstrated good solution quality and computational efficiency. The heuristics also balance workloads effectively without a substantial increase in delivery time.